Developing English Teaching Materials for Young Learners - Hertiki, Hertiki (JET ADI BUANA, 2018)
Teaching material is needed in teaching-learning activities in the classroom. Without an appropriate material, a teacher might have difficulty in delivering the lesson, especially for children. TEYL (Teaching English to Young Learners) is a compulsory subject for the English Department students of Adi Buana University and this course is only offered for the final year students. To support TEYL course, undergraduates need to create English Teaching Materials that are useful for both teacher and students in school. Therefore, it is important to conduct this study in order to develop English teaching materials that meet the students‟ need. The author concerns on the authentic teaching materials made by the undergraduates. The final product of English teaching materials for young learners are Let‟s Count and Clip, Boggle, Noun Clipboard, What Time is It?, and Dominoes Card. All in all, these English teaching materials have been used in one of the private schools (BP school) to help children learn English. Based on the result, it can be concluded that Let‟s Count and Clip as the most popular material among the children. It is quite attractive and appropriate to help grade three of primary school learn English.